Severe hypereosinophilia in a patient treated with dupilumab and shift to mepolizumab: the importance of multidisciplinary management. A case report and literature review - Sara Munari; Giulia Ciotti; Walter Cestaro; Lorenzo Corsi; Silvia Tonin; Andrea Ballarin; Ariel Floriani; Cristina Dartora; Annamaria Bosi; Matteo Tacconi; Francesco Gialdini; Michele Gottardi; et al. (BioExcel Publishing Ltd, 2024)
Type 2 inflammation is a heterogeneous condition due to the complex activation of different immunological pathways. Rapid progress in research to evaluate the efficacy of biologics for chronic rhinosinusitis with nasal polyps and asthma has led to the availability of effective therapeutic options. These drugs are safe, but temporary iatrogenic hypereosinophilia may sometimes be associated with clinical symptoms or organ damage. Here, we describe a case of severe hypereosinophilia in a patient with chronic rhinosinusitis with nasal polyps and asthma treated with dupilumab and a subsequent therapeutic shift to mepolizumab that led to maintenance of symptom control and concomitant normalization of blood eosinophil count.